FAKTOR PENTING PENINGKATAN DUKUNGAN DAN PARTISIPASI MASYARAKAT DESA PENYENGAT PADA KEGIATAN PERDAGANGAN KARBON KPHP TASIK BESAR SERKAP - Ervayenri, Ervayenri; Sadjati, Emy; Insusanty, Enny (Wahana Forestra: Jurnal Kehutanan, 2016)
This study aims to identify factors important to increase support and participation of village communities Penyengat on carbon trading in KPH Tasik Besar Serkap. The study was conducted from September 2015 until December 2015 involving 40 respondents in village of Penyengat Sungai Apit, Siak District, Riau Province. Data was collected through interviews using a structured questionnaire. The study states all respondents (100%) like to plant a tree. Types of trees planted by the respondents are fruits (33,33%), corn (22,22%), and forest plants (22,22%). In addition to plant rubber trees, palm or other forest plants, the majority of respondents (50,00%) to plant annual crops under the crop. Types of crops that are vegetables (50 ,00%). The seasonal crops majority (78,79%) and partly consumed by (6,06%) were sold to consumers around the village Penyengat. Most respondents (72,73%) had never heard of climate change / REDD +, only 15,15% of respondents who have heard through village officials (52,38%) and th e RT (14,29%). Most respondents (44,44%) did not know the meaning of REDD+ activities. If REDD+ activities are carried out, the potential of local institutions to i mplement is a farmer groups (33,33%), and public (33,33%). While other respondents (22,22%) could not give an answer about local agencies that have the potential to implement carbon trading activities in the village Penyengat. If REDD + activities be conducted, the training needs to be done a ccording to the respondents (71,43%) for the institution designated as administrators. Institutions that may be involved is a farmer groups (62,50%).